A Decade of Implementation of Android Media in Physics Learning - Fadhya Fadhya; Khairil Anwar; Linda Sekar Utami; Siti Alaa (JIPF (Jurnal Ilmu Pendidikan Fisika), 2023)
Android is very important in the learning process of natural sciences, especially in physics learning which is often called difficult so that a lot of research discusses its application in every level of education both at the elementary school, junior high school and high school levels. So far there has been no research that discusses further about how much influence the android media has in the process of learning physics. Therefore, the purpose of this study is to determine the degree of influence of the use of android media in physics learning for the last 10 years both at the elementary, middle and high school levels. This research uses a meta-analysis method, which is to analyze in depth the results of research that meet the established inclusion and exclusion criteria. The data was analyzed using JASP software with the input of Effect Size (ES) and Standard Error (SE) values. The results showed that overall the level of influence of android media in physics learning was 83% which is included in the high category. Based on the level of education at the elementary level, 95.3% (high category), junior high school by 73% (medium category), high school level by 84% (high category). The level of influence before Covid-19 was 85% (high category) and after Covid-19 was 82% (high category) and as for based on the focal plane of waves and optics by 71% (medium category), basic physics by 87% (high category) and thermodynamics by 85% (high category). So that when viewed based on the level of education, android media is more appropriate to use at the elementary level than junior high school and high school.